THU0432 Apremilast, An Oral Phosphodiesterase 4 Inhibitor, Is Associated with Long-Term (104-Week) Improvement in Fatigue in Patients with Psoriatic Arthritis: Pooled Results from 3 Phase III, Randomized, Controlled Trials. (15th July 2016) - Kavanaugh, A.; Gladman, D.D.; Edwards, C.J.; Poder, A.; Lioté, F.; Bird, P.; Schett, G.; Nguyen, D.; Teng, L.; Mease, P.J.
Abstract : Background: Fatigue, a common symptom affecting individuals with psoriatic arthritis (PsA), is associated with decreased quality of life and loss of work productivity. 1 The 2014 OMERACT PsA Working Group identified fatigue measurement as an important outcome to consider including in PsA core assessments. 2 The PALACE 1 (NCT01172938 ), 2 (NCT01212757 ), and 3 (NCT01212770 ) studies compared apremilast (APR) efficacy/safety, including fatigue level, with placebo (PBO) in patients (pts) with active PsA despite prior conventional DMARDs and/or biologics. Objectives: Report APR treatment impact on fatigue over 104 wks in a pooled analysis of the PALACE 1–3 studies. Methods: Pts were randomized (1:1:1) to PBO, APR 30 mg BID (APR30), or APR 20 mg BID (APR20) stratified by baseline DMARD use. The PBO-controlled phase continued to Wk 24, with a Wk 16 early escape option. At Wk 24, all remaining PBO pts were re-randomized to APR30 or APR20. Double-blind APR treatment continued to Wk 52; pts could then continue to receive open-label APR up to an additional 4 years. Fatigue was assessed using FACIT-F v4 and SF-36v2 Vitality domain (VT). 3 Total FACIT-F scores range from 0–52; lower scores denote higher fatigue levels. As a point of reference, mean fatigue scores of 40.1–43.6 in the general population, 4, 5 35.8 in PsA pts, 6 and 23.9 in anemic cancer pts 5 have been reported, and FACIT-F MCID in PsA has not been determined; this analysis used FACIT-F MCID in rheumatoid arthritis pts (3–4). 7 SF-36v2 VT, a subscale of SF-36v2, measures physical and mental impact of fatigue on individuals. 8 Scores are norm-based; group values <47 represent a below-average range vs the general population. 9 Results: Baseline mean FACIT-F (29.4–30.9) and SF-36v2 VT (40.6–40.8) scores were below population norms. Long-term improvement in fatigue was seen in APR pts at Wks 52 and 104 (mean FACIT-F=35.0), marking a shift toward population FACIT-F norms (Table ). APR30 mean change was 5.6, with 50.9% of pts achieving FACIT-F MCID. Similarly, improvements in SF-36v2 VT scores were observed at Wks 52 and 104 with ≈ 60% of pts achieving MCID. Over 104 wks, most AEs were mild/moderate; in general, no increase was seen in AE incidence/severity with longer term exposure. Conclusions: APR-treated pts experienced improvements in fatigue, as measured by FACIT-F and SF-36 VT scores. Over 104 wks, clinically meaningful improvements were maintained. APR demonstrated an acceptable safety profile and was generally well tolerated up to 104 wks. References: Swain. Clin Sci (Lond). 2000;99:1–8. Tillett. J Rheumatol. 2015;42:2198–2203. Yellen. J Pain Symptom Manage. 1997;13:63–74. Webster. Health Qual Life Outcomes. 2003;179. Cella. Cancer. 2002;94:528–38. Chandran. Ann Rheum Dis. 2007;66:936–9. Cella. J Rheumatol. 2005;32:811–9. Ware. Med Care. 1992;30:473–83. Advantages of norm-based scoring. In Ware, ed. User's Manual for the SF-36v2 Health Survey. 2nd ed. Lincoln, RI: QualityMetric Incorporated; 2007. Disclosure of Interest: A. Kavanaugh Grant/research support from: Abbott, Amgen, Astra-Zeneca, Bristol-Myers Squibb, Celgene Corporation, Centocor-Janssen, Pfizer Inc, Roche, and UCB, Consultant for: Abbott, Amgen, Astra-Zeneca, Bristol-Myers Squibb, Celgene Corporation, Centocor-Janssen, Pfizer Inc, Roche, and UCB, D. Gladman Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer Inc, Novartis, and UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer Inc, Novartis, and UCB, C. Edwards Grant/research support from: Celgene Corporation, Pfizer Inc, Roche, and Samsung, Consultant for: Celgene Corporation, Pfizer Inc, Roche, and Samsung, Speakers bureau: Abbott, Glaxo-SmithKline, Pfizer Inc, and Roche, A. Poder Grant/research support from: Celgene Corporation, F. Lioté: None declared, P. Bird Grant/research support from: Celgene Corporation, G. Schett Grant/research support from: Abbott, Celgene Corporation, Roche, UCB, Consultant for: Abbott, Celgene Corporation, Roche, UCB, D. Nguyen Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, P. Mease Grant/research support from: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, and UCB, Consultant for: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, and UCB, Speakers bureau: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, and UCB